Overcoming Dichotomies through Space: the Contribution of Dialectical Materialism to Organization Studies - S. Lacerda, Daniel (Organizações & Sociedade, 2015)
<!--[if gte mso 9]> 0 0 1 148 844 Lancaster University 7 1 991 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-GB JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} --> <!--[endif] --> <!--StartFragment--> One of the most debated choices of every social research design is the adoption of either a realist (objective) or an idealist (subjective) worldview of sociological problems. As argued in this paper, both perspectives can be embraced by the dialectical approach of historical space production, according to Marxists traditions in human geography. In order to show that, this paper explores the philosophical grounds of this debate, the attempts of conciliation of the dichotomy, and finally proposes a rejection of this dichotomy through the adoption of the categories of ‘space’ and ‘time’ as central in organizational analysis. Space is a historical production of social relations, and the same relations are defined by means of surrounding space. In that sense, organization studies can benefit of a spatial view of organizations to assist on the overcoming of epistemological constraints, by means of interpreting organizations as historically produced and part of the spatial context. <!--EndFragment-->